KUALITAS HADIS DAN PEMAHAMAN ULAMA TENTANG HATI - Sulaiman Muhammad Amir; Uqbatul Khoir Rambe; Muhammad Rasyid (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
This thesis describes the quality of hadith and the opinion of scholars about the heart, in humans it is the heart that has the potential to determine human identity itself. If he is clear he will guide the tongue to speak with soft words. If he is cloudy, he will force the tongue to issue bad and vile words. Departing from the problems and doubts about the validity of the hadith, the author tries to examine it by questioning several problems including how is the quality of the hadith about the heart, how are the opinions of scholars about the heart of the author using library research method. And the methodological steps that the writer takes are the maudhu'i method. This is an attempt to collect the traditions related to this research. then the author analyzes the data that has been found both from books and books, papers related to this research. The data collection method is the documentation method which seeks to collect all primary and secondary data. Primary data included in the Musnad Ahmad bin Hanbal, Sahih Al-Bukhori, Sahih Muslim Sunan Ad-Darimi, Sunan Ibn Majah or the book of syarah hadith. While the secondary data are Scientific Evidence in the Sunnah" by Zaghlul An-Najjar, "Religious Psychology" by Jalaluddin "Thibbil Qulub Clinic for Liver Disease" by Ibn Qayyim Al-Jauziyyah. The research concludes that the Sahih hadith both in terms of snad and matan, the narrator is tsiqoh, and is in line with jarh wa ta'dil and from the aspect of criticism, the hadith does not conflict with the verses of the Koran, does not conflict with other hadiths, does not conflict with science. , and does not conflict with Islamic history. Thus the hadith can be used as hujjah (legal backing).